YOUTH POLICY IMPLEMENTATION IN THE RUSSIAN FEDERATION: YOUTH PARTICIPATION IN NON-PROFIT ORGANIZATIONS - Vadim Alexeevich Batovrin (Вестник Северо-Кавказского федерального университета, 2022)
The peculiarity of the historical process in modern Russia is rapid development of non-profit organizations working in the sphere of youth policy. Youth social movement focused its attention on involving young people in the processes of forming the Russian society. Re-orientation of some powers and authorities from state to social institutes contributed to the optimization of youth non-profit organizations in decision making and political decisions realization in the youth policy sphere.